Electrochemical Studies on Speciation of Cadmium(II) in ppb Level by Complexation with Ethylenediamine in Aqueous Media - Nahar, Nurun; Ramim, Anshaya; Abser, M Nurul (Bangladesh Journal of Scientific and Industrial Research, 2009)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <![endif]--> <!--[if gte mso 10]> <![endif]--> The speciation of cadmium(II) in ppb level by complexation with ethylenediamine (EN) has been investigated by differential pulse anodic stripping voltammetry (DPASV) using thin mercury film coated glassy carbon electrode (TMFGCE). The overall work has been carried out at constant ionic strength of 0.01 mol dm-3 (NaNO3) at ambient temperature. The pH was kept constant at 8.81 ± 0.10 by the addition of borate buffer. The stability constants of different species of cadmium(II) with ethylenediamine have been calculated from the variation of peak potential and diffusion current of simple and complexed metal ions under the present experimental conditions. The logarithmic values of overall stability constants: log β1, log β2 and log β3 (βi = [CdLi]/[Cd2+][L]i where i = 1, 2 and 3) have been found to be 5.01, 8.9 and 11.1 for CdL, CdL2 and CdL3, respectively (charges were omitted for simplicity). The stability constants of cadmium complexes and hydrolysis constants of cadmium indicate that five different species of cadmium (Cd2+, CdOH+, CdL, CdL2 and CdL3) co-exist at ligand concentrations up to 5×10-4 mole dm-3 under the present experimental conditions. The results obtained by this method is applied to study the cadmium speciation in river water on the basis of competitive ligand exchange equilibrium. Key words: Speciation, Complexation, Aqueous media, DPASV, Mercury film electrode. doi: 10.3329/bjsir.v44i1.2709 Bangladesh J. Sci. Ind. Res. 44(1), 1-10, 2009